A very high amylase can be benign in paediatric Crohn's disease. (10th July 2012) - Venkataraman, Devasmitha; Howarth, Lucy; Beattie, Robert Mark; Afzal, Nadeem Ahmad
Abstract : A 12.5-year-old boy with Crohn's disease with abdominal pain had a raised amylase of 1835 IU/l with normal lipase levels. Ultrasound showed no evidence of inflammation of pancreas. The amylase to creatinine clearance ratio, was 0.8% (reference interval 2%–5%; >6% consistent with acute pancreatitis; <1.6% with macroamylasemia), suggesting he had raised serum amylase with a corresponding reduced clearance of amylase in his urine, positively supporting the diagnosis of macroamylasemia. Macroamylasemia has no clinical significance other than misdiagnosis as acute pancreatitis. Awareness of this condition is important and a positive diagnosis should always be made to avoid unnecessary changes in treatments.